Representasi Maskulinitas Hegemonik dalam Novel Ayah... Kisah Buya Hamka Karya Irfan Hamka: Kajian Kritik Sastra R.W. Connell - Rohman, Miftahul Afifur; Rengganis, Ririe; Sudikan, Setya Yuwana (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This research aims to uncover the form and function of hegemonic masculinity in intergender relationships so as to influence readers' understanding of the concept of masculinity. This research utilizes a qualitative approach to literary criticism of masculinity by Connell which was chosen because it is able to explain the power relations between men and between men and women. This study analyzes the dialogue and narrative in the Novel Ayah... Buya Hamka's story is through the technique of listening, purposive sampling, and the flow of Miles' analysis. The results of the study identified 35 findings divided into four categories: social constructs (25 findings) that show masculinity norms are shaped through cultural expectations; gender hierarchy (4 findings) that affirm the dominant position of men in intergender relations; the role of popular culture (1 finding) that reinforces masculine values from outside the text; and subordination (5 findings) that show the weakening of non-dominant forms of masculinity in order to maintain masculine hegemony. Overall, this study shows that the representation of masculinity in literature is intertwined with broader social and cultural structures. In addition, the recommendations of the study further explore the impact of hegemonic masculinity in other literary works and its influence on people's views on gender across cultural contexts.